Analysis of the fall point in table tennis game - Fei, Y.; Ushiyama, Y.; Jie, L.; Yu, Z. H.; Iizuka, S.; Kamijima, K. (International Journal of Table Tennis Sciences, 2010)
During a table tennis game, coaches give players some advice, based on their experience rather than objectivity. In this research, objective data are used to analyze the advice given to players. Coordinate data of the ball fall point in a National University Table Tennis Tournament, held in April of 2008, are analyzed with the help of a video camera. Attack and defensive patterns are analyzed, allowing weak points to be clarified. This research aims to extrapolate objective advice to the advice given by the coach from experience.